Antiplasmodial and antioxidant alkaloids from two lauraceae species, alseodaphne corneri and dehaasia longipedicellata, and the acid dissociation constant of selected bioactive alkaloids / Azeana Zahari - Azeana, Zahari (2016)

(untitled)
Preliminary survey of crude extracts of two Lauraceae species possessed potent antiplasmodial activities; Dehaasia longipedicellata (IC50=1.30 μg/mL), and Alseodaphne corneri (IC50=2.78 μg/ml). Twenty two compounds were successfully isolated and purified using extensive chromatography techniques. Purification of all alkaloids from crude extract of Alseodaphne corneri yielded sixteen alkaloids; reticuline 8, gyrolidine 18, 3, 4-dihydonorstephasubine 19, norstephasubine 20, N-methyllaurotetanine 26, laurotetanine 27, isocorydine 41, norisocorydine 42, thalrugosine 71, O-methyllimacusine 118, 2-norobaberine 115, 3, 4-dihydostephasubine 119, stephasubine 120, stephasubimine 121, N-methyllindcarpine 123, and one new compound; cornerin A 124, while, Dehaasia longipedicellata afforded eight alkaloids namely; reticuline 8, laurotetanine 27, norboldine 36, boldine 37, sinoacutine 29, milonine 46, sebiferine 47, and O-O-dimethylgrisabine 48. The structural elucidation of all the alkaloids were done by using spectroscopic techniques such as 1D-NMR (1H, 13C, DEPT), 2D-NMR (COSY, NOESY, HMQC, HMBC), UV, IR, MS and by comparison with the literature data. All compounds with sufficient amount (8, 18, 20, 27, 36, 37, 41, 42, 46, 47, 48, 115, 118, 120) were tested for antiplasmodial and antioxidant activities. As a result, norstephasubine 20 (0.116 μM), O-O-dimethylgrisabine 48 (0.031 μM) and laurotetanine 27 (0.189 μM) showed potent antiplasmodial activities. 48 had a higher potency with a lower IC50 value compared to the antimalarial drug, chloroquine, 0.090 μM. Antioxidant properties of a drug are beneficial to the host (human) as it could help as an additive therapy to reduce the side effects of malaria disease. Thus, these alkaloids have also been tested for their antioxidant activities using DPPH, FRAP and metal chelating assay. 48 showed the highest scavenging activity with an IC50 value of 28.75 μM when compared to the standard, BHA (77.73 μM). Furthermore, the most potent alkaloid, 48 apart from being potent antiplasmodial and antioxidant agents, is also not toxic towards normal pancreatic cell line, which makes it a good candidate for the drug development of malarial compounds. Three of the bioactive and highest yield alkaloids; 37, 41 and 42, were studied for acid dissociation constant using UV-vis spectrophotometry. The